Impact of Fermentation on Hyptolide and Phytochemical Composition of Hyptis pectinata (L.) Poit - Arie Adhi Nugraha; Lanni Rahma Aulia; Meiny Suzery; Agustina L. N. Aminin (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2024)
Solid State Fermentation has been employed for the biotransformation of the herbal plant Hyptis pectinata (L.) Poit is widely distributed in tropical regions of Brazil and is also present in Indonesia. The plant has been used to treat anti-inflammatory, anti-cancer, bacterial infection, and wound healing. This study aims to investigate the effects of using a solid-state fermentation method to ferment the leaves of Hyptis pectinata (L.) Poit towards the composition of phytochemicals and hyptolides. This study was carried out in several stages, including fermentation of Aspergillus niger leaves, sample extraction with methanol, determination of total phenolic and total triterpenoid content, phytochemical screening, and analysis of hyptolide using HPLC. The research results showed the growth of Aspergillus niger on the leaves of Hyptis pectinata (L.) Poit got into the logarithmic phase at 36 hours. Triterpenes and phenolics were present in the phytochemical profile, while alkaloids, tannins, and flavonoids were absent. The total phenolic and triterpenoid content increased by 33.68% and 17.78% respectively. HPLC analysis showed a decrease in hyptolide content in the fermented product. These results indicate the potential of fermented Hyptis pectinata (L.) Poit as an additional cancer therapy.